Antibacterial and antioxidant activity of endophytic fungi isolated from Peronema canescens leaves - ELFITA ELFITA; RIAN OKTIANSYAH; MARDIYANTO MARDIYANTO; HARY WIDJAJANTI; ARUM SETIAWAN (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Elfita, Oktiansyah R, Mardiyanto, Widjajanti H, Setiawan A. 2022. Antibacterial and antioxidant activity of endophytic fungi isolated from Peronema canescens leaves. Biodiversitas 23: 4783-4792. Peronema canescens Jack. or sungkai is a plant found in tropical rainforests. Also known as Peronema heterophyllum Miq., it belongs to the Verbenaceae family and grows widely in Thailand, Malaysia, and Indonesia. The local people believe that the antibacterial and antioxidant properties of its leaves increase immunity. Bioactivities of endophytic fungi associated with medicinal plants are currently of great interest due to their potential for development and use in the pharmaceutical, agricultural, and industrial fields. In this study, we investigated the antibacterial and antioxidant properties of an extract of leaves from P. canescens host plant and compared them with those of extracts from an endophytic fungus. Antibacterial and antioxidant compounds derived from active extracts of endophytic fungi have the capability to be developed as a source of antibacterial and antioxidant compounds equivalent to those of their host. In this study, endophytic fungi were isolated from the fresh tissue of P. canescens leaves and identified morphologically. Their antibacterial activity was tested using the Kirby-Bauer method, and their antioxidant activity was tested using the DPPH method. The potential antibacterial and antioxidant activities of the endophytic fungi extracts were identified molecularly, and the compounds were isolated using column chromatography. A structural determination of the antibacterial and antioxidant compounds was conducted by spectroscopy involving NMR 1D and 2D. Twelve of the endophytic fungi were gained from the P. canescens leaves, namely RD1-RD12. The RD6 isolate showed the greatest potential for antibacterial and antioxidant activity, and its molecular identification was expressed as Penicillium oxalicum. The pure compound produced was a yellowish white solid with strong antibacterial and antioxidant activity. Based on an analysis of spectroscopy NMR 1D and 2D, compound I was identified as 3-(2,6-dihydroxyphenyl)-2-hydroxyacrylic acid. The study demonstrated that endophytic fungi associated with medicinal plants and functioning as antibacterial and antioxidant agents have the potential to produce compounds as strong as those of the host plant. These compounds represent a potential new source for antibacterials and antioxidants.